Can shared practices build a new city? - Bianchetti, Cristina; Sampieri, Angelo (Journal of Architecture and Urbanism, 2014)
Contemporary living is increasingly marked by different kinds of associationisms, collective but not necessarily longlasting actions, and either little or very determined communalities. This article will discuss forms of living that reject individualism and shy away from communities. Indistinct forms, based on living “side by side, walking in step” which Bauman (2002) described as “a desperate need for networking”; and Sennett (2008) said was “the force of wandering emotions shifting erratically from one target to another”. Characterised by values such as ecology, frugality, reciprocity and solidarity. We believe that the key issue is to understand whether these forms are capable, as they say they are, of metaphorically rebuilding the city. In other words, can they implement a different concept of urbanity and public space by adopting the role played in late capitalist cities by conflict, rationality, functionalism, and the market. To tackle the problem we must first understand how they affect three different issues: the first involves changes in the values assigned to living; the second, the new logic of spatial organisation; the third, the revision of the notion of public and its political consequences. In order to provide greater clarity, we will deal with these three issues by briefly referring to European case studies carried out by a group of town-planners and sociologists.